Avaliação ambiental aplicável a bacias hidrográficas no meio urbano : análise dos métodos Amorim & Cordeiro, Pesmu e Swat - Junqueira, Cássia de ávila Ribeiro (2008)
The purpose of this research is to identify, systematize and evaluate three (3) methodologies applied to hydrographic basins and developed for the planning and management of the urban environment related to environmental concerns. The analyzed methods are some of the ones developed at the Federal University in Sao Carlos itself, such as PESMU and AMORIM & CORDEIRO, and a mathematical modeling with SWAT that interfaces with the ARCVIEW software. The research methodology was developed from the differences e similarities as for the used methods that were transformed in analysis criteria. These criteria were selected prioritizing the focus on the conditions that the evaluation method should offer to give support to the manager. For that reason, some characteristics, such as reliability, scientific validity, the standardization and accessibility of data were analyzed, so that, even when applied in different places, with distinct characteristics, there could be a comparison between answers in the different cases. The indicators of the methods were also analyzed to ascertain the range potential of the themes, their interpretability and representativeness. Other factors are also extremely important for managers, like application easiness and the type of cost involved in the analysis. The discussion about the results was carried out based on a critical text listing positive and negative aspects of the evaluated methods, besides a proposition of maintenance, elimination or alteration of the analyzed items, as well as of a systematization of the principal characteristics of each method. Before the performed analysis, the conclusion is that there is not a method that is the best one, but the most appropriate for each particular situation. While the AMORIM & CORDEIRO and PESMU methods have a more global focus for the diagnosis, the SWAT method analyzes the basin physical characteristics more deeply and becomes flexible in the interface with SIG. The three methods are complementary when it comes to that complex environment that is a hydrographic basin, since it contains interrelated physical, biological and social-economic information. The more complex the analysis, the greater the efficacy, but it also increases the cost and the response time, so all the characteristics should always be thought and pondered before the choice of the method or methods to be applied on a specific place. Besides, the existing input data should be checked so that the analyses do not become erroneous or subjective.